Mesoporous silica nanoparticles functionalized with fluorescent and MRI reporters for the visualization of murine tumors overexpressing αvβ3 receptors. Issue 13 (10th March 2016) - Hu, He; Arena, Francesca; Gianolio, Eliana; Boffa, Cinzia; Di Gregorio, Enza; Stefania, Rachele; Orio, Laura; Baroni, Simona; Aime, Silvio
Abstract : The developed nanoprobe (Gd–MSNs–RGD) shows good physiological stability, high relaxivity and a specific targeting capability toward U87MG tumor model in vivo . Abstract : A novel fluorescein/Gd-DOTAGA containing nanoprobe for the visualization of tumors by optical and Magnetic Resonance Imaging (MRI) is reported herein. It is based on the functionalization of the surface of small mesoporous silica nanoparticles (MSNs) (∼30 nm) with the arginine-glycine-aspartic (RGD) moieties, which are known to target αv β3 integrin receptors overexpressed in several tumor cells. The obtained nanoprobe (Gd–MSNs–RGD) displays good stability, tolerability and high relaxivity (37.6 mM −1 s −1 at 21.5 MHz). After a preliminary evaluation of their cytotoxicity and targeting capability toward U87MG cells by in vitro fluorescence and MR imaging, the nanoprobes were tested in vivo by T 1 -weighted MR imaging of xenografted murine tumor models. The obtained results demonstrated that the Gd–MSNs–RGD nanoprobes are good reporters both in vitro and in vivo for the MR-visualization of tumor cells overexpressing αv β3 integrin receptors.